Evaluation and comparison between the bactericidal effect of diode laser irradiation (970 nm) and silver nanoparticles on Enterococcus faecalis bacterial strain (an in vitro study) - Sadony, Doaa M. (2021)
There was a significant difference between the treated groups, in which the laser group showed a high bactericidal effect than the other groups at the time of radiation 40 s, without damaging the tooth structure or periodontal ligament. Diode laser with proper parameters is used as an adjunctive endodontic disinfection modality due to its antibacterial effect with a temperature tolerated by periodontal tissues with safety limit.